Are social media use and popularity in the peer group linked during adolescence? A meta‐analytic review - Schwartz, David; Zhang, Minci; Troop‐Gordon, Wendy; Taylor, Leslie M.; Chung, Jinsol (Journal of adolescence (London, England.), 2025)
Background Popularity in adolescence has been the subject of considerable empirical inquiry over the last two decades. As research on this dimension of social experience evolved, fundamental shifts occurred in the modalities through which adolescents communicate. Social networking platforms, instant messaging applications, and other forms of social media emerged as organizing features of adolescent peer groups. Objective In the current paper, we present a systematic review and meta‐analysis examining evidence that social media activity is associated with both popularity and goals for becoming popular. Methods Syntheses were conducted based on 34 effect sizes from 12 studies (N = 7776; 4037 girls and 3739 boys) using three‐level Meta‐analytic techniques. Results Average effect sizes across studies were of small to medium magnitude and were not influenced by Meta‐analytic moderators. Although the findings provide support for expected positive associations between social media activity and popularity, unresolved questions remain.